A bivariate extension of the beta generated distribution derived from copulas. Issue 5 (4th March 2019) - Samanthi, Ranadeera G. M.; Sepanski, Jungsywan
ABSTRACT: In this paper, we introduce a new class of bivariate distributions whose marginals are beta-generated distributions. Copulas are employed to construct this bivariate extension of the beta-generated distributions. It is shown that when Archimedean copulas and convex beta generators are used in generating bivariate distributions, the copulas of the resulting distributions also belong to the Archimedean family. The dependence of the proposed bivariate distributions is examined. Simulation results for beta generators and an application to financial risk management are presented.